Implementation Of an Academic Chatbot Based on Dialogflow for Study Program Information Services: A Qualitative Study on Usability and User Satisfaction - Ahmad Fakih; Fahmi Yuliady; Fatahillah Paweloi; Firanda; Gabriella Pasalli; Haerunnisa (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
The rapid development of artificial intelligence technology has encouraged the utilization of chatbot systems in higher education information services. However, the effectiveness of chatbot implementation in supporting academic information services requires evaluation, particularly in terms of usability and user satisfaction. This study aims to analyze the implementation of a Dialogflow-based academic chatbot and evaluate its usability and user satisfaction using a qualitative approach. This research employed a descriptive qualitative case study design. Data were collected through observation, in-depth interviews, and documentation involving 12 active students who had used the chatbot. Data analysis was conducted using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results indicate that the chatbot provides ease of access, fast response time, and relevant academic information. From a usability perspective, the system meets effectiveness, efficiency, and satisfaction aspects. However, several limitations were identified, including limited contextual understanding and restricted response variations. Overall, users expressed positive satisfaction and perceived the chatbot as helpful in supporting academic information services. The study contributes to the development of intelligent information systems in higher education by providing qualitative insights into user experience and system improvement strategies.